2010
DOI: 10.4236/jmmce.2010.99059
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Investigation of Damping Properties of Nano Particulate Composites

Abstract: Nano particulate composites with Al-Si alloys (LM6 and LM25) as matrix and Multiwall Carbon Nanotube (MWNT) as reinforcement (0.25, 0.5, 0.75, 1.0 and 1.5 weight percentage) have been fabricated by powder metallurgy process. Damping specimens were prepared according to ASTM E 756-05 standard and the specimens were subjected to free vibration test to investigate the damping ratio and natural frequency. It is observed from the free vibration test data; both alloys (LM6 and LM25) have shown significant improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Dynamic behaviors of the composite materials and structures were investigated in order to improve the damping behavior at high temperatures [ 12 , 13 , 14 ]. Many authors have investigated dynamic characteristics of composite materials and structures using free vibration methods [ 15 , 16 , 17 , 18 , 19 , 20 ]. Adding reinforcement particles to the metal matrix composites can change their mechanical and dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic behaviors of the composite materials and structures were investigated in order to improve the damping behavior at high temperatures [ 12 , 13 , 14 ]. Many authors have investigated dynamic characteristics of composite materials and structures using free vibration methods [ 15 , 16 , 17 , 18 , 19 , 20 ]. Adding reinforcement particles to the metal matrix composites can change their mechanical and dynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10].Vibration damping is one of the important requirements of the material when using it as machine base, frame, mountings and other supports. If the material's resistance to vibration or absorption of vibration energy is predominant, the ill effects in the mechanical systems will be greatly minimized [11][12][13][14].Vibration properties like damping factor and natural frequency of the Aluminium based composites were investigated by many researchers and reported that the reinforcements enhances the natural frequency and damping factor [13][14][15][16][17]. Mechanical behaviour like tensile, compression and flexural behaviour is analyzed with tungsten carbide reinforced aluminium composites [2] but no one reported wear and vibration analysis of tungsten carbide reinforcements with AA6061 aluminium alloy.…”
Section: Boronmentioning
confidence: 99%
“…The sintered material thus obtained was extruded through the die to obtain a product having a 10 mm diameter. The drawing speed during the extrusion process was maintained at 1.2 mm/second with an applied pressure of 21 MPa [8,9]. X-ray Diffractometer (XRD) (JEOL -JDX-8P) analysis of the procured LM6 alloy and the fabricated nanocomposites was carried out.…”
Section: Specimen Preparationmentioning
confidence: 99%